Using sensitivity and specificity of clinical signs and symptoms to triage possible soil-transmitted helminth infections in preschool children - Irma, Irma; Juniastuti, Juniastuti (Paediatrica Indonesiana, 2026)
Background The prevalence of pediatric soil-transmitted helminth (STH) infection in Kendari, Southeast Sulawesi remains high at 33.3%, well above the Indonesian national estimate of 21.6%. Laboratory confirmation of STH infection is often impractical and costly, posing problems for mass screening. Identification of signs and symptoms with high sensitivity and specificity can serve as a useful triage tool in resource-limited settings before laboratory confirmation. Objective To determine the diagnostic value of a specific set of signs and symptoms to screen for children to be prioritized for laboratory testing. Methods This cross-sectional study was conducted from October to December 2024 in the coastal areas of Kendari. The study involved 242 children from 8 early childhood education (PAUD) centers. We administered questionnaires to the mothers of participating children, followed by laboratory testing of their children. Five clinical signs and symptoms common to STH infection were analyzed and compared to laboratory findings as the gold standard. Results Not all children experienced signs and symptoms as reported by their mothers. The sensitivity, specificity, and accuracy of nausea/vomiting was 24.1%, 8.3%, and 11.1%, respectively, of frequent diarrhea was 17.2%, 95.3%, and 66.1%, respectively, of abdominal pain was 54.0%, 95.5%, and 80.5%, respectively, of anorexia was 47.1%, 87.7%, and 73.1%, respectively, and of frequent anal itching was 29.8%, 94.8%, and 71.9%, respectively. None of the symptoms had high sensitivity. However, abdominal pain, anorexia, and frequent anal itching showed relatively high specificity and accuracy, making them potentially useful for initial screening. Conclusion  Although no symptom alone can reliably detect STH infection, the presence of abdominal pain, anorexia, and anal itching may be considered as practical indicators for preliminary screening in resource-limited settings.